Purchasing behavior of UiTM Sabah student on instant noodles / Noor Ahmad Omar - Omar, Noor Ahmad (2006)
Instant noodles are dried precooked noodles fused with oil, usually eaten after being soaked in boiling water for 3 to 5 minutes. A flavor packet is usually included with a packet of instant noodles. The flavor packet usually contains monosodium glutamate, although MSG-free varieties can be found. The product may also be consumed raw from the packet, as the noodles are already cooked, usually by frying. The brick of noodles can be broken into squarish chunks before soaking or eating. If placed in hot water (such as from an office coffeemaker), 3 minutes in a microwave oven will cook them properly. Instant noodles originate from instant versions of the Japanese dish ramen, and retain that name in North America. However, as their popularity spread through Asia, other regional varieties that reflect the diversity of noodles available in the region have appeared, such as instant pho, instant beef noodle soup and instant rice vermicelli soup.